WEBSITE QUALITY ANALYSIS USING WEBQUAL 4.0 METHOD ON GARUDAKU WEBSITE - Maulana, Rivaldy; Prasetyo, Arfhan (Journal of Information System, Informatics and Computing, 2023)
PT. Garudaku Produk Kreatif is a creative production company that has pioneered in the esports industry in Indonesia. As a company that focuses on developing esports, PT. Garudaku Creative Production has a vision to expand the base of esports players in Indonesia by presenting quality and innovative products. Based on data taken at PT. Garudaku Creative Production recorded as many as 133 esports activists who actively access the Garudaku.com website. The Garudaku.com website is a website that provides information and content related to esports in Indonesia. This study measures the quality of the Garudaku.com website through the Webqual dimensions (usability, information quality, interaction quality) and user satisfaction variables, namely PT. Garudaku Creative Production. The data collection method uses primary data in the form of questionnaires distributed to 100 respondents. Data processing is done using SPSS. Based on data processing, it can be seen that the user's perception of ease of use, quality of information, quality of interaction is included in the pretty good category. Based on the research results, it was found that these three variables had a positive and significant effect on user satisfaction. From the research results, it can be seen that the information quality variable contributes the largest contribution, namely 52.18% of the other variables.